1997
DOI: 10.1099/00222615-46-1-85
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-associated bacterial flora of the human colon

Abstract: Edinburgh EH8 9AGBiopsy samples of mucosa were taken during colonoscopy from the proximal colon and rectum of 12 patients, six with ulcerative colitis (UC) and six with non-inflammatory conditions. After anaerobic transport to the laboratory, biopsy specimens were examined by quantitative bacteriological culture on selective and non-selective media for total aerobic count, total anaerobic count, Bacteroides spp., lactobacilli, bifidobacteria and asaccharolytic, lactic acid producers. Isolates of the genus Bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
6
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 22 publications
7
75
6
3
Order By: Relevance
“…In addition, reduced levels of bifidobacteria in the colorectal mucosa of patients with ulcerative colitis (a manifestation of IBD) have also been reported [26] . In general, our results on the occurrence and levels of total Bifidobacterium are in the range of those reported by Poxton and co-workers [25] in patients with ulcerative colitis. However, our study extends these observations to the level of Bifidobacterium species and differences in the species composition which may more accurately reflect the intestinal microbiota activity.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, reduced levels of bifidobacteria in the colorectal mucosa of patients with ulcerative colitis (a manifestation of IBD) have also been reported [26] . In general, our results on the occurrence and levels of total Bifidobacterium are in the range of those reported by Poxton and co-workers [25] in patients with ulcerative colitis. However, our study extends these observations to the level of Bifidobacterium species and differences in the species composition which may more accurately reflect the intestinal microbiota activity.…”
Section: Discussionsupporting
confidence: 75%
“…Only a few studies with mucosal samples have been conducted in both healthy individuals and patients [24,25] . In this area, the mucosal microbiota of patients suffering inflammatory conditions such as IBS and IBD is the most widely characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, metagenomic and microbiomic studies based on the analysis of genomic DNA-and rRNA gene libraries have highlighted the diversity of the GIT microbiota and have shown that it consists of many novel and, as yet, unculturable bacterial components (Eckburg et al, 2005;Wang et al, 2005;Gill et al, 2006;Kurokawa et al, 2007;Palmer et al, 2007). However, relatively few bifidobacterial rRNA gene sequences have so far been identified in these metagenomic studies, which are in striking contrast to what was described earlier in several bifidobacterial surveys, which had adopted culture-dependent approaches (Poxton et al, 1997;Harmsen et al, 2000;Fanaro et al, 2003).…”
contrasting
confidence: 46%
“…Some studies have found greater concentrations of coliforms and aerobic bacteria in patients with severe ulcerative colitis and moderate and severe CD, whereas other studies have reported a decrease in anaerobic and Lactobacillus species in patients with active IBD (31). An investigation of the rectal mucosa-associated bacterial flora in ulcerative colitis patients showed that both the highest bacterial counts and the highest isolation frequency were observed for B. vulgatus, Bacteroides fragilis, and Bacteroides ovatus, in that order (116). Changes in colonization patterns have also been observed (134,142), but the relative contributions of host and bacterial factors to this phenomenon remain to be elucidated.…”
Section: Bacteria In Ibdmentioning
confidence: 99%